2019
DOI: 10.1177/1354067x19871198
|View full text |Cite
|
Sign up to set email alerts
|

Psychological significance of Chinese myth of Yi: Signing and symbolizing, cultural and personal

Abstract: Chinese classical myth of “Yi” has accumulated in the long history as a huge and complex cultural imagery system with three levels. The first is the narrative level of mythological text and image; the second is the interpretation level of multi-leveled meaning through interpretation of Yi’s myth; the third is the application level of transferring and selecting specific meaning or employing/imitating certain narrative elements in different fields to achieve certain purposes. Around the three levels, this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Jungian analysts and Jungian‐oriented psychotherapists with a Chinese cultural background have integrated amplifications that include the relationship of yin and yang (resembling lunar and solar), and of the five elements in Chinese classical philosophy 2 . They have conducted qualitative studies on image and its development, for instance, the clinical practice of use of the mythic hero image (Guo et al, 2019, 2020). In the present study, this development is extended, so that the client's internal conflicts and personality integration are evaluated with reference to the development of opposing psychic contents or personalities and the interplay of these opposing elements.…”
Section: Methodsmentioning
confidence: 99%
“…Jungian analysts and Jungian‐oriented psychotherapists with a Chinese cultural background have integrated amplifications that include the relationship of yin and yang (resembling lunar and solar), and of the five elements in Chinese classical philosophy 2 . They have conducted qualitative studies on image and its development, for instance, the clinical practice of use of the mythic hero image (Guo et al, 2019, 2020). In the present study, this development is extended, so that the client's internal conflicts and personality integration are evaluated with reference to the development of opposing psychic contents or personalities and the interplay of these opposing elements.…”
Section: Methodsmentioning
confidence: 99%
“…Professionally, we accord more attention to the intersection of cultural narrative and personal narrative in psychological counseling. Through previous research (Guo, Shen, et al, 2019;Guo, Zhang, et al, 2020), we found that by using the interpretive framework of a certain psychological theory, the conceptualization and analysis of individual personalization of classical cultural images can provide insights into certain aspects of collective cultural psychology, and enable us to usefully assemble and structuralize the resources for psychological analysis found in collective culture.…”
Section: Introductionmentioning
confidence: 99%